Maternal employment effects of paid parental leave - Annette Bergemann; Regina T. Riphahn (Journal of Population Economics, 2022)
We study the short-, medium-, and long-run employment effects of a substantial change in Germany's parental leave benefit program. In 2007, a means-tested parental leave transfer program that paid benefits for up to 2~years was replaced with an earnings-related transfer that paid benefits for up to 1~year. The reform changed the regulation for prior benefit recipients and added benefits for those who were not eligible before. Although long-run labor force participation did not change substantially—the reform sped up mothers' labor market return after their benefits expired. Likely pathways for this substantial reform effect are changes in social norms and in mothers' preferences for economic independence.
Keywords: J13; J21; 330; Female labor supply; Maternal labor supply; Parental leave; Parental leave benefit; Child-rearing benefit